Pengaruh Disiplin Kerja Terhadap Kepuasan Kerja dengan Stres Kerja Sebagai Variabel Intervening pada Pegawai Samsat UPTB Pendapatan Wilayah Kabupaten Gowa - Nurjannah; Musa, Chalid Imran; Natsir, Uhud Darmawan; Sahabuddin, Romansyah; Nurman (CV. Lafadz Jaya, 2026)
This study aims to analyze the influence of work discipline on job satisfaction, both directly and indirectly through work stress as an intervening variable on employees of the Samsat UPTB Regional Revenue Office of Gowa Regency. The study used a quantitative approach with an explanatory research design. The study population included all employees of the Samsat UPTB Regional Revenue Office of Gowa Regency. The sampling technique used saturated sampling, so that all members of the population, totaling 46 employees, were used as research respondents. Data were collected through questionnaires and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the help of the SmartPLS application. The analysis was carried out through evaluation of the measurement model, evaluation of the structural model, and hypothesis testing to determine the direct and indirect effects between variables. The results of the study indicate that work discipline has a positive and significant effect on work stress and job satisfaction. Work stress also has a positive and significant effect on job satisfaction. In addition, the results of the indirect effect test indicate that work stress is able to significantly mediate the effect of work discipline on job satisfaction. These findings indicate that the implementation of work discipline and work stress management are important aspects in improving employee job satisfaction. Therefore, organizations need to implement disciplinary policies consistently while ensuring that job demands remain at a level that employees can manage.